The prevalence of early repolarization variant in Turkish male subjects: a clinical single center study - KEPEZ, ALPER; ERDOĞAN, OKAN (My University, 2012)
OBJECTIVES: Early repolarization variant (ERV) detected in surface ECG has traditionally been considered a benign finding, but the presence of this pattern has recently been associated with vulnerability to ventricular fibrillation in many case reports and case-control studies. There is no information regarding the prevalence of ERV within the Turkish population. The aim of this study was to evaluate the prevalence of ERV within a sample group of the healthy Turkish male population. STUDY DESIGN: We assessed the prevalence of ERV within a community-based general population of 504 healthy male subjects (mean age 37.3±10.7 years; range 18 to 55 years) using 12-lead electrocardiography. ERV was stratified by two independent cardiologists according to the J-point elevation (≥0.1 mV) in the inferior, lateral or both leads with QRS slurring or notching. RESULTS: The ERV pattern was present in 34 subjects (6.7%): 19 subjects (3.8%) displayed ERV in the lateral leads, 7 (1.4%) in the inferior leads, and 8 (1.6%) in both the lateral and inferior leads. CONCLUSION: The prevalence of ERV within the healthy Turkish male population seems to be similar to the findings of previous population-based studies.
Keywords: Humans; Prevalence; Male; Case-Control Studies; Electrocardiography; Ventricular Fibrillation